As influências culturais nas práticas alimentares da Comunidade Quilombola da Mutuca : território do Mata Cavalo - Silva, Laura Ferreira da (2023)
This study aims to discuss the cultural influences on the dietary practices of the quilombola community of Mutuca, located within the territory of Mata Cavalo, in the municipality of Nossa Senhora do Livramento (MT). The research employs a qualitative approach, encompassing analyses of production methods, the experiences within the quilombola territory, and traditional modes of farming and cultivation. As a methodology, it employs participant observation to demonstrate the paramount importance of food culture to the quilombola population – a place of voice, experience, customs, traditions, ways of life, and ancestral knowledge. Traditional knowledge holders play a role in preserving these practices, dynamically transmitting them to new generations through oral history and memory, which are integral to the quilombola experience in everyday life. The results indicate that these traditional systems contribute to cultural fortification and rights affirmation, leading to the conclusion that this practice is achieved by recognizing and showcasing quilombola families within the community and in the broader context.